1995
DOI: 10.1002/jor.1100130314
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis in cynomolgus macaques II. Detection of modulated proteoglycan epitopes in cartilage and synovial fluid

Abstract: The purpose of the present study was to determine the usefulness of the monoclonal antibodies 7-D-4 and 3-B-3 as biomarkers of severity of naturally occurring osteoarthritis in the knee joints of adult cynomolgus macaques. The antibodies were used to immunolocate chondroitin sulfate proteoglycan epitopes in articular cartilage or synovial fluid from knee joints with a range in severity of osteoarthritis. The joints were examined radiographically, grossly, microradiographically, and histologically to characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 16 publications
(21 reference statements)
3
35
0
Order By: Relevance
“…Specifically, concentration and presentation of the CS chains are important factors that need to be considered in the interpretation of 3B3(Ϫ) immunochemical assays. It may be particularly important to consider when comparing aggrecans by immunohistochemistry (21,23,38) or Western blotting after agarose acrylamide composite gels (15,20,22,24). For example, we have demonstrated that in nitrocellulose-based assays (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, concentration and presentation of the CS chains are important factors that need to be considered in the interpretation of 3B3(Ϫ) immunochemical assays. It may be particularly important to consider when comparing aggrecans by immunohistochemistry (21,23,38) or Western blotting after agarose acrylamide composite gels (15,20,22,24). For example, we have demonstrated that in nitrocellulose-based assays (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, although the data are not included in this study, sections of 13 knee joints were immunostained using the monoclonal antibody 7-D-4, which binds a chondroitin sulfate proteoglycan epitope that is a sensitive marker for early to mild lesions of OA in tissues from monkeys, dogs, and humans (21,34,35). Although these sections revealed focally increased 7-D-4 binding in areas of chondrocyte death and matrix degeneration, large numbers of chondrocytes in morphologically normal areas also exhibited positive staining, indicating that this technique would not be useful for identifying early articular cartilage lesions in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Like changes in background fluorescence, collagen denaturation products were first detected in the upper mid region of the cartilage and The association of the proteoglycan epitopes 7D4 and 3B3-with activation of an immature chondrocyte phenotype in OA cartilage has been controversial. The immunodetection of these proteoglycan epitopes has been shown to be enhanced in immature articular cartilage [14] and growth cartilage [6,14] and also in OA articular cartilage [29] and in animal models of OA [7,30]. However, a recent chemical analysis of the 3B3-epitope failed to detect any substantial change in OA cartilage [26] and suggested instead that immunodetection of the 3B3-epitope is influenced by clustering or unmasking of existing proteoglycan structures.…”
Section: Discussionmentioning
confidence: 99%